An Analysis of Movement Activities Curriculum and Achievement of Sustainable Development Goals in Kenya - Ruth Mugo Kahiga; Juliet Njeri Muasya (Newinera Publisher, 2022)
Research has shown that Physical education (PE) and sports programmes, currently referred to as Movement activities in the lower primary Competency Based Curriculum (CBC) in Kenya, impacts on the physical, mental, social and emotional growth of individuals. The programmes produce individuals who are competent, confident and endowed with knowledge, skills and attitudes for lifelong physical activity. To some extent, the programmes contribute to societal development, which leads to the achievement of Sustainable Development Goals (SDGs). The aim of the current analysis was to find the extent to which movement activities in CBC is geared towards the achievement of the SDGs using Posner’s curriculum analysis framework. Research findings show that the curriculum is committed to achieving the SDGs for instance, good health and quality education. Maintaining the commitment and determination in implementing the movement activities curriculum will go a long way in actualizing the SDGs in Kenya.